Clinical impact of the hepatitis C virus mutations in the era of directly acting antivirals. Issue 10 (29th March 2016) - Coppola, Nicola; Minichini, Carmine; Starace, Mario; Sagnelli, Caterina; Sagnelli, Evangelista
Abstract : Introduced in 2013–2014, the second‐ and third‐wave directly acting antivirals (DAAs) have strongly enhanced the efficacy and tolerability of anti‐HCV treatment, with a sustained virological response (SVR) in 90–95% of cases treated. The majority of patients who did not achieve an SVR were found to be infected with HCV strains with a reduced susceptibility to these drugs. Indeed, the high error rate of the viral polymerase and a fast virion production (100‐fold higher than the human immunodeficiency virus) result in a mixture of viral genetic populations (quasi‐species) pre‐existing treatment initiation. These mutants occur frequently in the NS5A region, with a moderate frequency in the NS3/4A region and rarely in the NS5B region. Treatment‐induced resistant mutants to NS5A DAAs persist for years after treatment discontinuation, whereas those resistant to the NS3 DAAs have a shorter duration. This review focuses on the type and prevalence of viral strains with a reduced sensitivity to DAAs, their clinical impact and influence on the response to treatment and, consequently, on treatment choice for DAA‐experienced patients. J. Med. Virol. 88:1659–1671, 2016 . © 2016 Wiley Periodicals, Inc.